2007
DOI: 10.1136/ard.2006.065128
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of epicutaneous ketoprofen in Transfersome (IDEA-033) versus oral celecoxib and placebo in osteoarthritis of the knee: multicentre randomised controlled trial

Abstract: Objective: To compare epicutaneous ketoprofen in Transfersome (ultra-deformable vesicles, IDEA-033) versus oral celecoxib and placebo for relief of signs and symptoms in knee osteoarthritis. Methods: This was a multicentre, randomised, double-blind, controlled trial; 397 patients with knee osteoarthritis participated and 324 completed the trial. They were randomly assigned 110 mg epicutaneous ketoprofen in 4.8 g Transfersome plus oral placebo (n = 138), 100 mg oral celecoxib plus placebo gel (n = 132), or both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 18 publications
2
66
1
1
Order By: Relevance
“…The excipients of TDT 067 are widely used in pharmaceutical and cosmetic products for topical application, and clinical studies involving more than 2,000 patients with different diseases have shown that Transfersome preparations are well tolerated (2,16,22). Furthermore, in two phase II clinical studies of TDT 067 in patients with onychomycosis, treatment was well tolerated, and most patients did not experience application site reactions (6,27).…”
mentioning
confidence: 99%
“…The excipients of TDT 067 are widely used in pharmaceutical and cosmetic products for topical application, and clinical studies involving more than 2,000 patients with different diseases have shown that Transfersome preparations are well tolerated (2,16,22). Furthermore, in two phase II clinical studies of TDT 067 in patients with onychomycosis, treatment was well tolerated, and most patients did not experience application site reactions (6,27).…”
mentioning
confidence: 99%
“…In study CL-033-II-03, pain relief was reported with both IDEA-033 and TDT 064, but superiority of IDEA-033 to TDT 064 in improving physical function was not shown [7]. Marked clinical improvements in pain were also reported in study CL-033-III-02 with both IDEA-033 and TDT 064; pain relief was greater with IDEA-033 than TDT 064, but not improvements in physical function [10].…”
Section: Discussionmentioning
confidence: 51%
“…Topical formulations of ultradeformable phospholipid vesicles containing ketoprofen have been shown to be effective. 29 …”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 97%